Bat–bat fly interactions in Central Panama: host traits relate to modularity in a highly specialised network. Issue 5 (18th May 2021) - Hiller, Thomas; Vollstädt, Maximilian G. R.; Brändel, Stefan D.; Page, Rachel A.; Tschapka, Marco
Abstract: Recently, network approaches have gained increasing popularity in studies of species interactions. These analyses provide important information about structural and functional organisation, as well as on the dynamics of species interactions. Common model systems for network studies include seed dispersal, pollination, and also parasite interactions. Bat flies (Diptera: Streblidae, Nycteribiidae) are obligate blood‐sucking ectoparasites of bats. Resource partitioning allows multiple fly species to co‐occur on a single host individual, making them an ideal model system for network analyses. Between 2013 and 2018 in Central Panama, 6528 bats from 53 species were examined for the presence of bat flies. Thereof, we collected a total of 6077 bat flies belonging to 52 species. The resulting interaction network showed a significantly higher specificity ( H 2 ' = 0.97) and modularity ( Q  = 0.78) than expected by chance, indicating a very high host specificity of the bat flies. To investigate parasite interactions in the context of host size, host abundance and roosting preferences, we pooled parasite identifications on genus level. The majority of our identified modules were associated with bats using persistent roosting structures. Neither host size nor host abundance appeared to affect module structure. Further, module structure appeared not to be host‐phylogeny driven, instead modules were often composed of species known to share roosting structures. Their high host‐specificity could put bat flies at risk of extinction in changing environments. Abstract : Network analyses of 6528 bats associated with 6077 ectoparasitic bat flies revealed extremely high host specificity, with organisation of the network in small subsets reflecting a highly modular network structure. Module structure appeared not to be host‐phylogeny driven, instead modules were often composed of bat species known to share roosting structures. The high host‐specificity of these obligate bat parasites may put them at risk of extinction in changing environments.